STUDYING THE EFFECT OF SCINTILLATION DETECTOR RESPONSE BASED ON MONTE CARLO SIMULATION - BIDALO (NIM : 20216010), FITRIAH
Simulation of the effect of scintillation detectors with natrium iodide (NaI), Thalium activated Sodium Iodide NaI(Tl), bismuth germanate (BGO), and Cerium Activated Litetium Axy-orthosilite (LSO:Ce) was conducted using the Monte Carlo methode with user code is a tutor3.mortran and aided by the EGSnrcMP GUI software program. The simulation was done by modeling the geometry of the detector in 3 dimensions as a cube, where the surface width was defined as infinite in the XY direction but was limited in the Z direction by the stickness of the material. The methode of studying the crystal material used is a conventional method, but it can observe the effect of the stickness of the matrial and measure the source of radiation energy. By differentiating the sources based on energy, there were 3 energy variations, namely 1.17 MeV and 1.33 MeV for the ?Co?^60 sources, and 0.662 MeV for the ?Cs?^137 sources. The stickness of the material was varied (at 1.27 cm, 2.54 cm, 5.08 cm, and 7.62 cm), so that in total 48 simulation result were generated. The analysis was devided into 3 stages based on the effect of the material, the effect of the stickness, and the effect of energy variation, respectively. The simulation result showed that based on the material effect, the attenuation coefficient decreased with increasing energy (E). The error percentage of the gradient value that identifies the relationship between the gradient and the material absorption coefficient based on the NIST database and the simulation results, namely NaI of 2.91%, and BGO of 17.95%. Based on the stickness variation, the intensity of the photon radiation source increased with the stickness of the scintillator material. From the ratio between thw stickness of the scintillation material and the value of Ln(Io/I). The linear attenuation of Ln(Io/I) from the simulation data was the gradient value. The gradien identifies the relationship between the gradient and the absorbtion coefficient. The highest absorption value by BGO material is 0.0998 / cm, and the lowest by NaI material is 0.0499 / cm. The detector was simulated to measure the characteristics of the Cs137 source and the ?Co?^60 source based on the energy variation, which showed that the energy value corresponded to the characteristics of the radiation source. fluence photons (intensity) experience attenuation by the material of the scintillator so that the absence of photons escapes. Photons that escaped increase with the increase in photon energy. BGO material has the best response among the scintillator materials used in this simulation. The simulation result also showed that the EGSnrc user cofde was in the form of tutor3.mortran. a sensor based on MC methode can simulate the process in the detector well to determine the response of the scintillation detector material.